Presidential Decree-Law No. 54 of the year 2014 On Amending Certain Provision of Law No. 121 of the Year 2008 Amending the Traffic Law promulgated by Law No.66 of the year 1973 = قرار رئيس الجمهورية بالقانون رقم 54 لسنة 2014 بتعديل قانون 121/2008 بتعديل قانون المرور رقم 66 لسنة 1973 / presidency - Egypt. presidency (2025)
Presidential Decree-Law No. 54 of the year 2014 On Amending Certain Provisions of law no. 121 of the year 2008 Amending the traffic law promulgated by law no. 66 of the year 1973 قرار رئيس جمهورية مصر العربية بالقانون رقم 54 لسنة 2014 بتعديل بعض أحكام القانون رقم 121 لسنة 2008 بتعديل قانون المرور الصادر بالقانون رقم 66 لسنة 1973